2010
DOI: 10.1158/1055-9965.epi-10-0288
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Laboratory Model for Evaluating the Acute Effects of Electronic “Cigarettes”: Nicotine Delivery Profile and Cardiovascular and Subjective Effects

Abstract: Background: Electronic "cigarettes" are marketed to tobacco users as potential reduced exposure products (PREP), albeit with little information regarding electronic cigarette user toxicant exposure and effects. This information may be obtained by adapting clinical laboratory methods used to evaluate other PREPs for smokers.Methods: Thirty-two smokers participated in four independent Latin-square ordered conditions that differed by product: own brand cigarette, "NPRO" electronic cigarettes (NPRO EC; 18 mg cartr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
354
4
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 346 publications
(385 citation statements)
references
References 33 publications
(45 reference statements)
21
354
4
4
Order By: Relevance
“…Of these, 13 articles met inclusion criteria for this review [49][50][51][52][53][54][55][56][57][58][59][60][61]. One article reported on the clinical outcomes of interest (two cases of MI) [49].…”
Section: Research Question #2mentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 13 articles met inclusion criteria for this review [49][50][51][52][53][54][55][56][57][58][59][60][61]. One article reported on the clinical outcomes of interest (two cases of MI) [49].…”
Section: Research Question #2mentioning
confidence: 99%
“…One article reported on the clinical outcomes of interest (two cases of MI) [49]. Eleven articles measured heart rate and BP after EC exposure [50][51][52][53][54][55][56][57][58][59][60]. In 5 of these articles, investigators followed participants for at least 1 week [49,[57][58][59][60], but in 7 articles, authors only reported acute outcomes (changes over b 5 h of exposure) [50][51][52][53][54][55][56].…”
Section: Research Question #2mentioning
confidence: 99%
See 3 more Smart Citations